Speech Acts in the Apprentice Asia TV Program - Muhammad Reza Pahlevi; Amrin Saragih; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2015)
This study is concerned with the use of speech acts in The Apprentice Asia TV program. The objectives of this study were to describe, to explain the types of speech acts used by the host, advisors and contestants of The Apprentice Asia, and the reasons. The findings of this study showed that all types of speech acts, namely representative, directive, commissive, expressive and decalarative were used by the host and contestants, while the advisors did not use expressive and declarative. The dominant type of speech act used by the host was directive, while the advisors and contestants dominantly used representative speech act. The participants performed them by direct, indirect, literal and non-literal way. There were some reasons of using types of speech acts used by all participants. In order to get information from other participants about the performances of the contestants in running the task, type of speech acts used by the host was directive in the form of questioning. On the other hand, the advisors and contestants were the participants whose informations required by the host. Therefore, in responding what the host asked to them, they performed their speech acts through representative in the forms of informing. Key words : Apprentice Asia; Speech Acts;and TV program.